2012
DOI: 10.1159/000333562
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evidence of Cross-Reactivity between Cow’s Milk and Soybean Proteins in a Mouse Model of Food Allergy

Abstract: Background: Cow’s milk allergy (CMA) is an important problem worldwide and the development of an in vivo system to study new immunotherapeutic strategies is of interest. Intolerance to soybean formula has been described in CMA patients, but it is not fully understood. In this work, we used a food allergy model in BALB/c mice to study the cross-reactivity between cow’s milk protein (CMP) and soy proteins (SP). Methods: Mice were orally sensitized with cholera toxin and CMP, and then challenged with CMP or SP to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 76 publications
0
57
1
13
Order By: Relevance
“…[25] The same recommendation was reaffirmed in the updated document of 2008 [26]. Furthermore, it was recently shown that CM-sensitized mice without previous exposure to SP elicited hypersensitivity signs immediately after the oral administration of SP, suggesting that immunochemical cross-reactivity might be clinically relevant [27]. Consistent with these indications, Irastorza et al [14] did not allow their patients to ingest soy.…”
Section: Discussionmentioning
confidence: 99%
“…[25] The same recommendation was reaffirmed in the updated document of 2008 [26]. Furthermore, it was recently shown that CM-sensitized mice without previous exposure to SP elicited hypersensitivity signs immediately after the oral administration of SP, suggesting that immunochemical cross-reactivity might be clinically relevant [27]. Consistent with these indications, Irastorza et al [14] did not allow their patients to ingest soy.…”
Section: Discussionmentioning
confidence: 99%
“…33,12 Briefly, recombinant U-Omp16 was isolated from bacterial cytoplasm and then purified by affinity chromatography with a Ni-NTA resin (Qiagen). Expression and purification of the recombinant protein was checked by SDS-PAGE followed by Coomasie Blue staining and to confirm the identity of the U-Omp16, western blot was performed and developed with anti-Omp16-specific mAb (data not shown).…”
Section: Micementioning
confidence: 99%
“…33 Briefly, mice received 6 weekly intragastric (i.g) doses of 20 mg of CMP administered as homogenized commercial non-fat dry milk, plus 10 μg of cholera toxin (CT) (Sigma Aldrich) in a final volume of 200 μL of bicarbonate buffer (sensitized mice). As control group naïve mice received 6 weekly i.g doses of 20 mg CMP with PBS.…”
Section: Sensitization and Treatment Of Micementioning
confidence: 99%
See 2 more Smart Citations